THE NEXT STEP: THE INTEGRATION OF ENERGY LAW AND ENVIRONMENTAL LAW (Utah Environmental Law Review; Vol 31 No 2 (2011), 2011)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} For many years, the law has largely ignored the obvious connection between energy production and consumption and nature. The laws that govern energy in this country-energy law-have very little to do with the laws that restrict what can be done with nature-environmental law. The primary focus of energy law is to ensure that energy is supplied without disruption at an affordable price. The primary focus of environmental laws is to be sure that the process of creating anything, including energy, does not create "too much" pollution, however we might define that phrase. The question motivating this conference is what the future of energy law holds. I contend that, acknowledging the realities of how energy is created and the critical and pressing question of climate change, energy law must become more integrated with environmental law. Indeed, I will argue that we need to reimagine energy policy in a way that draws on much of the best thinking in both energy law and environmental law circles, but that creates an integrated energy and environmental law. My hope is that such a law will streamline the requirements for energy producers and make clear to the public what our collective energy choices mean for nature.